Virtual Reality in Biology Assessment: Constructing and Standardizing an Achievement Test for Virtual Rat Dissection - Sarpal, Simmi; Nangia, Anita (PT. Riset Press International, 2025)
This study presents a detailed process of designing and validating of the biology achievement test for class XI students. The investigator first framed 77 items from the class XI biology NCERT textbook. After writing test items, the researcher consulted subject experts to make sure the items were well-structured, free of language errors, and had the right difficulty level. Incorporating the expert suggestions, a preliminary draft of 80 test items was developed. This preliminary draft was then administered to 100 biology students in private CBSE schools in Chandigarh for item analysis. The difficulty value (DV) and item discrimination (DP) were established using Kelley's (1939) method. Based on item analysis, 38 items were retained in the achievement test. The average item difficulty of the test was calculated as 0.54, and the average item discrimination was 0.49. A high-reliability coefficient of .87 was obtained for the test. The test’s validity was supported through expert evaluation and content validation. The results showed that the biology achievement test is both highly reliable and valid for assessing class XI students' understanding of biology.